Preliminary Study of the Antimicrobial Capacity of the Cutaneous Mucus and Smear Cytology of the Epidermis in a Population of European eels (Anguilla anguilla, Linnaeus 1758) - Enrico Volpe; Sara Ciulli; Maria Morini; Laura Gentile; Antonio Casalini; Chiara Gentilezza; Luciana Mandrioli (Animals, 2025)
The skin and its products, such as the mucus, represent an important defense mechanism against infection by pathogens. Various environmental conditions can alter mucus composition and/or cells embedded in this matrix. The analysis of skin mucus is considered a useful method to evaluate the biological response of fish to stimuli. The mucus and cells can be considered suitable non-invasive biomarkers. With this preliminary study, an antibacterial capacity method was applied to cutaneous mucus samples of a European eel population. This standardized method highlighted the ability of the mucus to significantly counteract the proliferation of two bacteria, the opportunistic pathogen Aeromonas hydrophila and the primary pathogen Aeromonas salmonicida. The cytological method using skin scraping has proven to be a useful non-invasive tool, having allowed the highlighting of the two most represented cellular populations of the cutaneous covering, the epidermal cells and the goblet cells, in combination with mucous strands. Cytological findings did not disclose pathologic elements in the mucus. A broader use of these two non-invasive microbiological and cytological methods can provide useful information on fish health, indirectly contributing to the conservation of the species.